Ancient Daoist Wisdom and Its Associated Principle of Yin-Yang for Contemporary Classrooms as Foundations for a Harmonious World - McLachlan Jeffrey, David (Philosophical Inquiry in Education, 2021)
This article focuses on ancient Daoist wisdom, together with its associated principle of yin-yang, and their contemporary significance in terms of how they might be applied within today’s classrooms as foundations for a harmonious world. It does so by illustrating the significance of Daoism and yin-yang from both historical and philosophical perspectives, as well as highlighting their spread to the West in relatively recent years in which growing numbers of classroom teachers are applying Daoist wisdom in their classrooms. It then suggests further approaches through which teachers might continue applying Daoist wisdom towards a harmonious yin-yang balance based on the associated Daoist principles of the virtue-less virtue of de and the naturalness of ziran, as well as the effortlessness of wuwei and the universal abundance of qi energy.